The Effect of Marketing Mix on Repurchase Intention with Customer Satisfaction as a Moderation Variable (Study on Braud Bali Cafe) - Manyasa, Komang Merta Mulia; Wardana, I Made; Suprapti, Ni Wayan Sri; Triaryati, Nyoman (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine the influence of price perception, product quality, service quality, place, and promotion on repurchase intention, with customer satisfaction as a moderating variable, in a case study of customers at Braud Café Bali. A quantitative approach using survey methods with moderation tests was employed for data analysis. The results indicate that price perception, product quality, service quality, and place have a positive and significant effect on repurchase intention. In contrast, promotion shows no significant effect. Furthermore, customer satisfaction does not moderate the relationship between the independent variables (price perception, product quality, service quality, place, and promotion) and repurchase intention. These findings suggest that aspects of quality and accessibility play a more critical role in driving repurchase decisions than promotional efforts or customer satisfaction as a moderating factor.